Особливості функціонування ритейлу в прифронтових регіонах - Венгерова, Олена Василівна; Venherova, Olena (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У статті визначено частку суб’єктів господарювання, що займаються ритейлом у прифронтових регіонах, в загальній кількості роздрібних торгівельних підприємств України. Підкреслено особливості релокації підприємств, що займаються роздрібною торгівлею. Досліджено особливості функціонування ритейлу в прифронтових регіонах України. Встановлено, що прискорена цифровізація та омніканальність стали механізмами адаптації сучасного ритейлу. Визначено, що на здатність ритейлу здійснювати свою діяльність у прифронтових регіонах значний вплив справляє державна підтримка. Розглянуто основні ризики, які впливають на діяльність ритейлу у прифронтових регіонах. Сформульовано пропозиції щодо зменшення існуючих ризиків для ритейлу в прифронтових регіонах. Обґрунтовано, що комплексне поєднання логістичної диверсифікації, цифровізації, гнучкого управління асортиментом і державної підтримки дозволяє знизити системні ризики в ритейлі. /// EN: The article determines the share of business entities engaged in retail trade in frontline regions within the total number of retail enterprises in Ukraine. It has been established that risks associated with military actions affect the vast majority of businesses engaged in retail trade. The specific features of retail enterprise relocation are highlighted. The study examines the characteristics of retail functioning in the frontline regions of Ukraine. It has been established that despite the high risks of operating in frontline regions, the opportunity to generate income for enterprises and entrepreneurs remains high. It is substantiated that frontline territories are characterized by the restructuring of supply routes, a reduction in the product portfolio, and the dependence of recovery rates on the level of security. It is established that accelerated digitalization and omnichannel strategies have become key adaptation mechanisms for modern retail. It has been determined that frontline regions exhibit lower numbers of retail outlets, slower recovery rates, and reduced investment activity. The study reveals that frontline regions are marked by the dominance of food and socially essential goods, reduced demand for non-food categories, and increased price competition. The study shows that competition between traditional retail and e-commerce is increasing. This is particularly relevant for regions with damaged infrastructure, where online channels can partly offset the limited physical access to retail outlets. The research shows that state support has a significant impact on retail businesses' ability to operate in frontline regions. The main risks affecting retail activities in frontline regions are analyzed. Proposals to reduce existing risks for retail businesses in these regions are being developed. It is substantiated that a comprehensive combination of logistics diversification, digitalization, flexible assortment management, and state support enables reducing systemic risks and ensuring the continuity of trade activities even amid increased security uncertainty.
Specific features of retail functioning in frontline regions
Keywords: ритейл; роздрібна торгівля; прифронтові регіони; суб’єкти господарювання; ризики; релокація; цифровізація; омніканальність; retail; retail trade; frontline regions; business entities; risks; relocation; digitalization; omnichannel strategy